The influence of popular music, in particular urban grooves lyrics on the Zimbabwean youth: the case of the Troika, Maskiri, Winky D and Extra Large - Viriri, Advice; Viriri, Agnella; Chapwanya, Carter (Taylor and Francis (Routledge) with Unisa Press, 2014)
This article critically examines the influence of popular music, especially urban grooves lyrics, on the youth of Zimbabwe, focusing in particular on the lyrics of Alishas ‘Maskiri’ Musimbe, the duo Extra Large and Wallace ‘Winky D’ Chirimuko. Some of these lyrics at first glance appear to be humorous, but a deeper analysis reveals a destructive message. The article explores the socio-cultural influence of these urban grooves artists in Zimbabwe and whether urban grooves music is indeed the ‘music of the people, about the people and by the people themselves’ (Kwaramba 1997, 2). It investigates the role music plays in the socialisation of the Zimbabwean youth and the extent to which it influences the behavioural trends of the youth in urban communities in particular.